The Role Of Local Industry Innovation In Growth Economy In Area Cianjur Regency - Kirena Az-Zahra Muchtar; Shifwah Khoirunnisa; Muhamad Rayhan (IFADAH : Jurnal Ekonomi Dan Bisnis Syariah, 2026)
Regional economic growth is largely determined by the ability of a region to manage as well as develop potential local Which owned. Cianjur Regency as a region dominated by the agricultural sector has great opportunities for development. local industry, especially micro, small and medium enterprises Agricultural-based micro, small, and medium enterprises (MSMEs). However, to date, this potential has not fully contributed optimally to improving the regional economy due to low product added value and limited innovation in the processing sector. This study aims to examine the role of local industrial innovation in driving economic growth in Cianjur Regency through an approach. studies literature. Data study obtained from various source Secondary sources include national and international scientific journals, official reports, and research institution publications relevant to local product innovation, strengthening MSMEs, agricultural product differentiation, and regional economic transformation. The study results indicate that local industrial innovation, including product innovation, production processes, and digital marketing, can increase the added value of agricultural products, expand employment opportunities, and strengthen regional competitiveness and economic resilience. Furthermore, institutional support and local government policies play a crucial role in creating a sustainable innovation ecosystem. Therefore, local industrial innovation can be viewed as a key strategy in driving inclusive and sustainable regional economic growth in Cianjur Regency